Sifat Fisik dan Kimia Pupuk dari Limbah Kulit Ubi Kayu (Manihot utillissima) dengan Aktivator Tricholant - Yuanita (Buletin Loupe, 2020)
Waste or rubbish is the result of disposal from a production process both small and large scale. Because of the smell and its negative impact on health, it has become a big problem in society. One problem is cassava waste. With a lot of unused cassava waste, especially fried food selling areas around the city of Samarinda. A good solution is to make fertilizer from sewage. The purpose of this study was to observe the physical properties of fertilizers (color, odor, shape and temperature) and chemical properties or to analyze the nutrient content of fertilizer from cassava peel using a tricholant activator and chicken manure. Based on the physical properties of cassava peel fertilizer (Manihot utillissima) with a tricholant activator decompose on day 9, with a stable temperature of 27OC, the structure of black crumbs, odorless, and crumbs. The resulting fertilizer is ripe and ready to use. The resulting fertilizer is ripe and ready to use. The results of chemical fertilizer analysis in the first treatment (cassava waste with tricholant activator) had N content of 1.20% N, P 0.801%, K 0.302%, C / N ratio 17.35, BO 27.17% and pH 6.8 and fertilizer with the second treatment (mixing cassava waste with a mixture of tricholant activator and chicken manure) has nutrient content N 0.81%, P 0.134%, K 0.235%, C / N ratio 19.2, BO 30.75% and pH 7 in accordance with SNI 19-7030 -2004 fertilizer quality standards